2015
DOI: 10.1186/s12870-015-0697-9
|View full text |Cite
|
Sign up to set email alerts
|

The hybrid non-ethylene and ethylene ripening response in kiwifruit (Actinidia chinensis) is associated with differential regulation of MADS-box transcription factors

Abstract: BackgroundRipening in tomato is predominantly controlled by ethylene, whilst in fruit such as grape, it is predominantly controlled by other hormones. The ripening response of many kiwifruit (Actinidia) species is atypical. The majority of ripening-associated fruit starch hydrolysis, colour change and softening occurs in the apparent absence of ethylene production (Phase 1 ripening) whilst Phase 2 ripening requires autocatalytic ethylene production and is associated with further softening and an increase in ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 61 publications
(92 reference statements)
5
48
0
Order By: Relevance
“…Ethylene-induced kiwifruit ripening involves the increased expression of ethylene biosynthesis and perception genes (Giovannoni, 2004(Giovannoni, , 2007Kim et al, 1999;McAtee et al, 2015;Sfakiotakis et al, 1997). In this study, transcript levels of AcACS1 and AcACO2 drastically increased in propylene-treated fruit at day 5 while no increases were observed during storage and on the vine (Fig.…”
Section: Expression Of Ethylene Biosynthesis and Perception Genesmentioning
confidence: 70%
See 2 more Smart Citations
“…Ethylene-induced kiwifruit ripening involves the increased expression of ethylene biosynthesis and perception genes (Giovannoni, 2004(Giovannoni, , 2007Kim et al, 1999;McAtee et al, 2015;Sfakiotakis et al, 1997). In this study, transcript levels of AcACS1 and AcACO2 drastically increased in propylene-treated fruit at day 5 while no increases were observed during storage and on the vine (Fig.…”
Section: Expression Of Ethylene Biosynthesis and Perception Genesmentioning
confidence: 70%
“…However, significant ripening of kiwifruit with undetectable ethylene production has been previously reported when fruit are left on vine after commercial harvest date (McAtee et al, 2015;Murakami et al, 2015;Richardson et al, 2011). However, the mechanism of the on-vine ripening has not been elucidated.…”
Section: On-vine Ripening In 'Rainbow Red' Kiwifruitmentioning
confidence: 94%
See 1 more Smart Citation
“…McAtee et al (2015) identified nine ethylene receptors in the 'Hongyang' genome, five of which have been published (Yin et al 2008). However, further analysis showed that two gene models did not have the all the receptor domains and one was truncated (McAtee et al 2015).…”
Section: Ethylene-signalling Genesmentioning
confidence: 96%
“…These transgenic lines should also be a useful tool to determine the role of ethylene (if any) during the rapid phase 1 of softening. McAtee et al (2015) mined the recently published kiwifruit genome (Huang et al 2013) to identify genes associated with ethylene biosynthesis and identified ten SAM synthetase genes, only one of which had previously been identified (Whittaker et al 1995). identified thirteen putative ACC synthase genes in the 'Hongyang' predicted coding sequence database, including the ACS1 gene identified by Whittaker et al (1997).…”
Section: Ethylene Biosynthetic Genesmentioning
confidence: 97%